Language experiences of hearing individuals with D/deaf parents: Polish Sign Language as their heritage language - Kotowicz, Justyna; Tondos, Klaudia; Wodniecka, Zofia (Papers in Linguistics, 2021)
Hearing individuals of D/deaf parents (CODA, child of D/deaf adult) simultaneously acquire two languages: a sign language from their D/deaf parents and a spoken language through contact with hearing individuals. It is important for CODAs’ bilingualism that it concerns two languages with a different status: a heritage language, namely a sign language used by D/deaf community members, and a spoken language, an official language of the country used by the majority. The aim of the undertaken analysis was to describe the specificity of CODAs’ language experience in three domains: language acquisition, language skills and language mediation experience. The data collected concerned two languages: Polish Sign Language (PJM, polski język migowy) and Polish (spoken language); the Language Questionnaire for CODA was used. The results showed that PJM has not been dominated by Polish (spoken language); on the contrary, PJM is important for CODAs’ communication, and its significance is expressed by the following factors: early acquisition, high competence, daily usage, and long-term mediation experience. The conclusions apply to a specifically recruited group of participants who took part in the project on CODAs’ bilingualism and, for this reason, further investigation is needed to formulate general conclusions on CODAs population.